Forensik WhatsApp Menggunakan Metode Digital Forensic Research Workshop (DFRWS) - Anton Yudhana; Imam Riadi; Riski Yudhi Prasongko (Politeknik Harapan Bersama, 2022)
Smartphone technology makes cybercrime crimes increase from year to year, one of the smartphone applications used to commit crimes is WhatsApp. The WhatsApp application is one of the most widely used social media, especially in Indonesia. Criminal acts such as hate speech, fraud, and defamation often occur on WhatsApp social media. This research was conducted to find forensic evidence on the WhatsApp social media application using the Digital Forensics Research Workshop (DFRWS) method. The stages of digital forensics include identification, preservation, collection, examination, analysis and presentation in finding digital evidence of cybercrime using the MOBILedit Forensic Express and HashMyFiles software applications. The digital evidence sought on smartphones can be found using case scenarios with 13 parameters that have been created. The results of this study indicate that the digital forensic software MOBILedit Forensic Express can detect types of digital evidence with an accuracy rate of 84.6%, while Hashmyfiles can detect the authenticity of digital evidence by 100%.